Life cycle assessment of burger patties produced with extruded meat substitutes. (15th July 2021) - Saerens, Wiebe; Smetana, Sergiy; Van Campenhout, Leen; Lammers, Volker; Heinz, Volker
Abstract: Extruded meat substitutes, due to their high protein content, meat-like texture and meat processing compatibility, are very popular as the main ingredient of plant-based burger patties. The extrusion of plant-based proteins can be performed by two technologies: high moisture extrudates (HME) and low moisture texturized vegetable proteins (TVP). The largest difference between the technologies relates to the moisture content prevailing inside the extrusion barrel. The extrusion processes also vary in their throughput, and yields. Life cycle assessment (LCA) was performed to compare the environmental performance of the two extrusion technologies applied to two plant-based raw materials (soymeal and pumpkin seed flour). Additionally, the study compared plant-based burger patties to meat burger patties (beef, pork and chicken). The impact of plant-based burger patties was at least ten-fold lower than meat burger patties. TVP-production exhibited a higher environmental impact compared to HME (20–40% higher depending on the raw material). The best performing plant burger patties were HME-soy-patties, in contrast with the worst-performing plant TVP-soy patties. TVP-pumpkin seed patties presented lower impacts compared to TVP-soy ones. Graphical abstract: Image 1